Sporesat: a nanosatellite platform lab-on-a-chip system for investigating gravity threshold of fern-spore single-cell calcium ion currents - Wan Salim, Wan Wardatul Amani; Park, Joon; Rickus, Jenna; Radamacher, Abraham; Ricco, Antonio (Transducer Research Foundation (TRF), 2014)

(untitled)
SporeSat – a lab-on-a-chip (LOC) centrifuge platform designed for integration as the payload of a small (5.5 kg), free-flying satellite – has been developed to determine the gravitational thresholds for calcium-ion channel activation of a single-cell spore from the fern Ceratopteris richardii. This fern is an important model system for gravity-directed plant-cell development during variable-gravity conditions attainable only in space flight. Calcium-ion channel activity is measured by photolithographically defined calcium ion–selective electrodes (ISEs) at opposite ends of each spore. Artificial gravity is created by rotating a disk-like platform that contains the spores in wells along with the calcium ISEs. Ground experiments reveal a maximum calcium concentration ratio at 2.2xg, between micro-ion-selective electrodes near the “top” and “bottom” ends of the spore, indicating an increasing calcium concentration at one “end” of the fern spore with respect to the other. Confocal micrographs of rhizoid formation confirm the light-induced germination. SporeSat is a spaceflight experiment that will take ~ 4 days; data will be telemetered to Earth over ~ 100 days.